PEMBERDAYAAN MASYARAKAT MELALUI KULIAH KERJA NYATA (KKN) DI DESA KEDUNG PENGAWAS KECAMATAN BABELAN KABUPATEN BEKASI MELALUI PROGRAM ECO PRINT DAN DIGITALISASI UMKM - Alwi Sihab; Shafira Nabiilah; Aulia Panji Laksamana; M. Essa Millan Ramadhan P; Auli Choiriyah (Jurnal Padamu Negeri, 2026)
The Tri Dharma of Higher Education finds one of its most tangible expressions in the Community Service Program (KKN), which allows students to actively engage with and support local communities empowerment and development. This initiative was carried out by Group 82 of Bhayangkara University of Greater Jakarta in Kedung Pengawas Village, Babelan Subdistrict, Bekasi Regency, with a focus on the Ecoprint program and the digitization of MSMEs. The implementation methods included field observation, socialization, participatory education, training, and community assistance. The programs consisted of two main activities: (1) Ecoprint training as a medium for developing community creativity through the utilization of environmentally friendly natural materials; and (2) socialization and assistance in MSME Digitalization through the use of social media and digital marketing as promotional tools. The results of the activities showed an increase in participants' creativity in producing Ecoprint-based artworks and an improvement in MSME owners’ understanding of the importance of digital marketing in expanding market reach. These activities provided positive impacts on enhancing community skills, fostering environmentally based creativity, and strengthening the capacity of MSME actors in adapting to technological developments. Through collaboration among university students, village officials, and local communities, this KKN program is expected to encourage the development of a more creative, productive, and adaptive society in facing future challenges